2017
DOI: 10.21037/jss.2017.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar endoscopic lateral recess decompression—surgical technique and early clinical results

Abstract: Background: Lateral recess stenosis is a common pathology causing de-novo or residual radicular pain following lumbar spine surgery. Diagnostic criteria and treatment strategies for symptomatic lateral recess stenosis are not well established. Methods:We identified ten patients in our prospective patient database (n=146) who underwent endoscopic interlaminar decompression for unilateral symptomatic lateral recess stenosis. Lateral recess height and angle were measured on axial T2-weighted MRI. Values from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Previously, we have emphasized the significance of spinal full-endoscopic system not only for LDH, but also lumbar foraminal stenosis (8) and symptomatic discal pseudocysts (20). Other investigators have also reported the operative indication of this system for other spinal diseases, such as lateral recess stenosis (21) and lumbar aneurysmal bone cyst (22). In this report, we have also proved the significance of this system even for lumbar LFH.…”
Section: Discussionsupporting
confidence: 65%
“…Previously, we have emphasized the significance of spinal full-endoscopic system not only for LDH, but also lumbar foraminal stenosis (8) and symptomatic discal pseudocysts (20). Other investigators have also reported the operative indication of this system for other spinal diseases, such as lateral recess stenosis (21) and lumbar aneurysmal bone cyst (22). In this report, we have also proved the significance of this system even for lumbar LFH.…”
Section: Discussionsupporting
confidence: 65%
“…The full-endoscopic ULBD technique has been previously described by the senior author. 9 Briefly, sequential dilators are used to create a tubular path in which a beveled working cannula is placed, followed by a working-channel spinal endoscope (iLESSYS Delta, Joimax, Vertebris stenosis, RIWOSpine). Under direct endoscopic visualization, a high-speed diamond burr is used to create an ipsilateral laminotomy extending to the base of the spinous process, exposing the ligamentum flavum.…”
Section: Surgical Techniquementioning
confidence: 99%
“…50 Endoscopic decompression has been developed as an extension of transforaminal and interlaminar discectomy. 4 A recent cadaveric study demonstrated that the transforaminal approach combined with an extensive foraminoplasty allowed access to the lateral recess both ventral and dorsal to the traversing nerve root. 85 Minimally invasive tubular decompression for lumbar spinal stenosis has demonstrated favorable reduction in Oswestry Disability Index and leg pain while maintaining a low complication profile.…”
Section: Lumbar Endoscopic Unilateral Laminotomy For Bilateral Decompmentioning
confidence: 99%